Sources of innovation funding in Polish companies in the light of statistical surveys - Aldona Małgorzata Derén; Jan Skonieczny (Economic and Environmental Studies (E&ES), 2018)
One of the key components of the innovation management process is selection of sources of funding innovative projects in the company. The research problem taken up by the authors is important for Polish companies, especially SMEs, which base their strategies upon innovations. The analysis of publications concerning strategic choices confirms the existence of a relatively small number of scientific and research studies within this area. Thus, there is a cognitive gap, which encouraged the authors to carry out analyses of the research problem defined in this manner. The purpose of the article is to discuss the criteria and variants of strategic selection of the funding sources of innovations in a company. Based on the experience of others, described in the literature, and their own analyses, the following criteria were adopted: market development, type of innovation and potential sources of its financing. Then, the process of selecting sources of financing innovation was developed. The article analyses the available literature, internet data, results published in the European Innovation Scoreboard 2017 and statistical data prepared by the Polish Central Statistical Office (GUS) regarding sources of financing innovations. It enabled separation of sources of financing innovations in Polish enterprises and assessment of their applications in the practice of business.The obtained results indicate that despite the existence of various innovation funding sources, Polish companies are definitely dominated by their own financing. There is a small contribution of public and external funds.
Keywords: G24; L0; O10; 330; enterprise; market; innovation; innovation funding sources